Effect of glycerol on the lipids in the red alga Gratelupia doryphora. - A. P. Ivanova; R. R. Robaina; J. Martín; K. L. Stefanov (Grasas y Aceites, 1999)
The red alga Gratelupia doryphora was cultivated in Provasoli enricher (plain) seawater and in a glycerol media. The incubation in seawater leads to an increase in the percentage of polyunsaturated acids, while the glycerol increase the total lipid content. If the alga is being grown as a heterotrophic culture, it is possible to increase the alga biomass as well as the content of biologically-active fatty acids.